MO042: Biallelic variants in TTC21B as a rare cause of early-onset arterial hypertension and tubuloglomerular kidney disease. (3rd May 2022) - Olinger, Eric; Phakdeekitcharoen, Pran; Caliskan, Yasar; Mabillard, Holly; Pickles, Charles; Tse, Yincent; Wood, Katrina; Sayer, John
Abstract: BACKGROUND: Massively parallel sequencing (MPS) has propelled precision medicine into the next generation. With genetic data more accessible than ever, the focus has now shifted from obtaining data to converting the acquired data into applicable clinical information. A major obstacle to such task arises when there is limited knowledge of the phenotypic spectrum of a genetic entity, limiting the application of virtual panels and prioritization of genetic candidates. METHOD: We performed in-depth clinical, imaging and histological phenotyping of an index family presenting with extremely early-onset hypertension and kidney disease. We then performed genetic investigations on the proband, starting with a limited MPS panel testing for monogenic causes of arterial hypertension. This was followed by Genomics England 100 000 Genomes Project whole genome sequencing (WGS) and application of a 26-gene virtual panel for 'extreme early-onset hypertension'. Subsequently, we reviewed the 100 000 Genomes Project rare disease data for patients recruited with extreme early-onset hypertension. We also conducted a literature review to identify any existing studies correlating TTC21B mutations and systemic hypertension. RESULTS: The proband (Table 1, II.1) was a 3.5-year-old girl presenting with severe hypertension, proteinuria, kidney failure, left ventricular hypertrophy, liver function test abnormalities and growth retardation. A kidney ultrasound scan showed bilateral small kidneys with loss of corticomedullary differentiation. Kidney biopsy showed sclerosed glomeruli, severe tubular atrophy with tubulointerstitial fibrosis in addition to arteriolar changes in secondary to systemic hypertension. Her sibling (Table 1, II.2) equally presented with early-onset hypertension and progressive kidney disease. MPS panel testing and WGS virtual panel for early-onset hypertension both failed to identify pathogenic variants. Manual curation of WGS data then revealed a heterozygous nonsense variant p.(Gln834Ter) in conjunction with a heterozygous missense variant p.(Pro209Leu) in TTC21B, both of which were predicted to be pathogenic according to ACMG criteria. This was missed as the gene did not form part of the hypertension virtual panel. TTC21B mutations have been previously associated with typical ciliopathies such as nephronophthisis (NPHP) and Jeune asphyxiating thoracic dystrophy, but only recently implicated in glomerular kidney disease such as focal segmental glomerulosclerosis (FSGS). Literature review suggests roles for TTC21B (IFT139) both in the primary cilium and in podocyte cytoskeleton, revealing a striking association between TTC21B missense variants and early-onset hypertension. Searching the 100 000 Genomes Project revealed one additional case of arterial hypertension and mild proteinuria explained by biallelic mutations in TTC21B . CONCLUSION: In conclusion, biallelic mutations in TTC21B produce a spectrum of phenotypes from typical ciliopathies to kidney-limited phenotypes. The latter are mostly encountered in patients carrying two missense, often hypomorphic, variants, and are characterized by lesions of the glomerular as well as the tubulointerstitial compartment, resembling both FSGS and NPHP. Increased clinical recognition of this mixed glomerular and tubulointerstitial disease with often mild or absent features of a typical ciliopathy as well as inclusion of TTC21B on gene panels for early-onset arterial hypertension may shorten the diagnostic odyssey for patients affected by this rare tubuloglomerular kidney disease.